Global Internet Governance: Influences from Malaysia and Singapore by Susan Leong and Terence Lee - Tan Lee Ooi (Kajian Malaysia, 2021)
The issue of internet control, regulation or governance has been exhaustivel studied, with near-conclusive findings repetitively drawn from various cases. Discussion on how the internet is governed has statically taken a two-sided framework, namely liberal versus authoritarian. Hence, it is an immense challenge for contemporary scholars to open up a new perspective or academic debate on this subject. The mission to seek a plurality of approaches in understanding the topic will allow researchers to understand complexities and consequences of the media world without taking any politically correct standpoint on this subject with respect to policies of any country or government.